Obstructive sleep apnea severity and pathophysiological traits in overlap syndrome: Insights from the SNOOzzzE cohort - Janna Raphelson; Ana Sanchez‐Azofra; Jeremy E. Orr; Gabriela Parra; Lana McGinnis; Alexis Salinas; Steven Luu; Scott A. Sands; Ali Azarbarzin; Robert L. Owens; Jose M. Marin; Atul Malhotra; et al. (Physiological Reports)
Abstract The overlap syndrome (OVS), defined as coexisting chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA), is linked to worse outcomes than either condition alone. Patients with COPD and OSA may have fewer obstructive events, but underlying mechanisms remain unclear. Using a large clinical cohort, we tested the hypothesis that OSA severity and pathophysiological traits differ in OVS versus OSA‐alone. Data from the SNOOzzzE cohort (3319 adults with in‐laboratory polysomnography 2017–2019) were used. OVS patients were identified through chart review and matched to OSA‐only patients (3:1) by age, sex, and body mass index. OSA severity was assessed using apnea hypopnea index (AHI), hypoxic burden (HB), and T90 (%time with SpO2 < 90%), while OSA traits were quantified from polysomnographic signals via validated algorithms. Mixed model analysis quantified group differences before and after adjustment for covariate differences (Black race, smoking) accounting for matching as a random effect. In our diverse cohort (103 OVS vs. 309 OSA‐only; 38% women, 44% non‐White, 17% Hispanic), OVS patients tended to have a lower AHI and HB (approximately −10%, p < 0.1), but significantly higher T90 (~50%, p = 0.003). OVS patients had less upper airway collapsibility, lower arousal threshold, lower ventilatory response to arousal (p < 0.05) and tended to have higher upper airway dilator muscle compensation (p = 0.09). In adjusted analyses, effect estimates were similar, but significance was attenuated. Hyperinflation and air trapping were inversely associated with AHI/HB. OSA severity and mechanisms differ in OVS versus OSA‐only. Future research should seek to evaluate these differences for their prognostic ability.